Hidradenocarcinoma eccrinale syringomatodes of the eyelid – case of a rare malignancy - Ziaja, Karolina; Pogrzebielski, Arkadiusz; Orłowska-Heitzman, Jolanta; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Presentation of a case of very rare malignant tumor of eccrine sweat glands in the eyelid. Material and methods: A 44 years old man with a tumor of the upper left eyelid is presented. Conclusions: Sweat gland carcinomas are rare malignant tumors of the skin adnexa. Diagnosis of these carcinomas is difficult due to their infrequency.